2010
DOI: 10.2298/sarh1008430s
|View full text |Cite
|
Sign up to set email alerts
|

The influence of stress hyperglycaemia on the prognosis of patients with acute myocardial infarction and temporary electrical cardiac pacing

Abstract: The best cut-off value for SH in patients with AMI (STEMI) and temporary electrical cardiac pacing is 10 mmol/l (determined by ROC curve) and may be used in risk stratification; patients with glucose levels <10 mmol/l on admission are at 3-fold lower risk compared to those with glucose levels >10 mml/l. Our results suggest that SH is a more reliable marker of poor outcome in AMI patients with temporary pace maker, without previously diagnosed DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…94 There has also been a recent focus on biomarkers and tools to predict the risk of stress hyperglycaemia, future diabetes and outcomes from intervention. 95 Higher cortisol levels have been found to be predictive of the onset of stress hyperglycaemia 96 as well as of subsequent normalisation of blood glucose levels. 97 In the case of the latter it is suggested that higher cortisol levels reflect stress-precipitated hyperglycaemia whereas lower cortisol levels suggest 'underlying glucose intolerance' as the most likely explanation for hyperglycaemia.…”
Section: Hyperglycaemia In Acute Myocardial Infarctionmentioning
confidence: 99%
“…94 There has also been a recent focus on biomarkers and tools to predict the risk of stress hyperglycaemia, future diabetes and outcomes from intervention. 95 Higher cortisol levels have been found to be predictive of the onset of stress hyperglycaemia 96 as well as of subsequent normalisation of blood glucose levels. 97 In the case of the latter it is suggested that higher cortisol levels reflect stress-precipitated hyperglycaemia whereas lower cortisol levels suggest 'underlying glucose intolerance' as the most likely explanation for hyperglycaemia.…”
Section: Hyperglycaemia In Acute Myocardial Infarctionmentioning
confidence: 99%
“…However, hyperglycaemia in a critically ill [4] or postoperative patient [5] may have various detrimental effects on the host’s defence system: blood glucose levels >180 mg/dl (10 mmol/l) have a compromising effect on the immune system [6]; the immune responsiveness of the mononuclear phagocytic cells is depressed; neutrophil function is impaired; the inflammatory response is exaggerated; and the immune system is weakened, thus increasing susceptibility to infection [7]. Recent evidence has proved that perioperative (intraoperative plus postoperative) hyperglycaemia is directly correlated with the development of deep sternal wound infection, increased mortality and morbidity, and increased hospital stay [8].…”
Section: Introductionmentioning
confidence: 99%